A pancreatic mixed neuroendocrine-non-neuroendocrine neoplasms (MiNEN) (NET and undifferentiated carcinoma of the pancreas with osteoclast-like giant cells) with metastatic neuroendocrine component to the liver - Guofeng Gao; Amir Qorbani; Chihong Heidi Zhou (University of São Paulo, 2021)
Undifferentiated carcinoma of the pancreas with osteoclast-like giant cells (UCOGCs) is an extremely rare morphologically and clinically distinct variant of pancreatic ductal adenocarcinoma (PDAC), exhibiting a characteristic component of reactive osteoclast-like giant cells admixed with neoplastic mononuclear cells. Sommers and Meissner first described it in 1954 as an "unusual carcinoma of the pancreas". Later it acquired many different names. In 2010, the WHO classified these tumors as a variant of PDAC under the heading of "undifferentiated carcinoma with osteoclast-like giant cells". Here we describe the first case of pancreatic mixed neuroendocrine-non-neuroendocrine neoplasms (MiNEN) composed of UCOGC and pancreatic neuroendocrine tumor (NET), which occurred in a 78-year-old man with biliary colic and pancreatitis. The mass did not respond to the chemotherapy, and he soon developed liver metastasis from the NET component, and unfortunately, the patient passed away 10 months later. Since UCOGC is extremely rare, and its association with NET has not been reported yet, our case expands the knowledge regarding its unusual presentation and poor prognosis.